Bacteriological evaluation of conjunctiva, contact lens storage cases and solutions during contact lens wear - Prabha, Vijay; Singh, N; Chopra, P (Indian journal of pathology & microbiology, 2007)
A total of 90 subjects were investigated in this study, out of which 51 constituted the contact lens wearing group and 39 constituted the control group who had never worn contact lenses. Out of 51 contact lens wearing group, 41 were asymptomatic lens wearer subjects and 10 were symptomatic lens wearer subjects having some complications. All the subjects of contact lens wearing group had worn soft contact lenses on daily wear basis for a duration of 7 days to one year. In total 33 subjects were culture positive and remaining 57 culture negative. Staphylococcus epidermidis was isolated equally from asymptomatic and control group, however, significantly more gram negative organisms such as Pseudomonas aeruginosa and Serratia marcescens were isolated from the symptomatic lens wearers. P. aeruginosa and S. marcescens could also be isolated from lens storage cases. S. marcescens was the organism most commonly isolated from the contact lens solutions. Further, the results showed that both P. aeruginosa and S. marcescens adhere to injured cornea only and not to normal cornea when microscopic study of adherence of bacteria to uninjured and injured ex vivo mouse corneas was done.